2014
DOI: 10.1111/obr.12184
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of primary caregivers reports on lifestyle behaviours of European pre‐school children: the ToyBox‐study

Abstract: SummaryReliable assessments of health-related behaviours are necessary for accurate evaluation on the efficiency of public health interventions. The aim of the current study was to examine the reliability of a self-administered primary caregivers questionnaire (PCQ) used in the ToyBox-intervention. The questionnaire consisted of six sections addressing sociodemographic and perinatal factors, water and beverages consumption, physical activity, snacking and sedentary behaviours. Parents/ caregivers from six coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(100 citation statements)
references
References 22 publications
2
96
1
1
Order By: Relevance
“…Four studies examined intake among older adults, namely MEDIS (MEDiterranean Islands Study) (78) , the Seven Countries Study (4,91,92) , SENECA (Survey in Europe on Nutrition and the Elderly; a Concerted Action) (43,90,148,149) and the 'Food in later life' study (68) . Nine studies assessed intake among children (27,30,37,50,85,86,101,116,120) in age ranges 2-9 years (37,118,119) , 3-6 years (95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106) , 2-11 years (50) , 7-11 years (116) , 11 years (85) and 10-12 years (27) , and seven assessed intake among adolescents (32,50,109,110,(113)(114)(115) .…”
Section: Public Health Nutritionmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies examined intake among older adults, namely MEDIS (MEDiterranean Islands Study) (78) , the Seven Countries Study (4,91,92) , SENECA (Survey in Europe on Nutrition and the Elderly; a Concerted Action) (43,90,148,149) and the 'Food in later life' study (68) . Nine studies assessed intake among children (27,30,37,50,85,86,101,116,120) in age ranges 2-9 years (37,118,119) , 3-6 years (95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106) , 2-11 years (50) , 7-11 years (116) , 11 years (85) and 10-12 years (27) , and seven assessed intake among adolescents (32,50,109,110,(113)(114)(115) .…”
Section: Public Health Nutritionmentioning
confidence: 99%
“…A pre-coded 24-HDR, FFQ X (42,136) X ToyBox (95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106) 6 (Belgium, Bulgaria, Germany, Greece, Poland, Spain) Children's FFQ X (137) (124) No validation data for F&V…”
Section: Ffqmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this was partially covered by ensuring anonymity. In addition, González-Gil et al have studied the reliability of primary caregivers' reports and concluded that 'a primary caregivers questionnaire is a reliable tool to assess socio-demographic characteristics, perinatal factors and lifestyle behaviours of pre-school children and their families participating in the ToyBoxintervention' (p. 61) (49) . The FFQ of Huybrechts et al, on which the FFQ used in the present study was based, was specifically designed for use by parents of pre-school children.…”
Section: Discussionmentioning
confidence: 99%
“…First, the large study sample of preschool children from six European countries and three socioeconomic strata, as well as the fact that immigrant participants were included in the study sample, comprise strengths of the study. Moreover, overweight/obesity was based on objective measures conducted by rigorously trained researchers who achieved excellent intra-and interobserver reliability and defined according to one common criterion applied for all countries [32], and the questionnaires (to record sociodemographic, perinatal, and behavioral data) had "moderate-to-excellent reliability" [33]. On the other hand, the cross-sectional design of the study prohibits from the identification of cause-effect associations.…”
Section: Tablementioning
confidence: 99%